2023
DOI: 10.1021/acs.jcim.3c00183
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Thermogravimetric Data in Bromine Captured from Brominated Flame Retardants (BFRs) in e-Waste Treatment Using Machine Learning Approaches

Abstract: The principal objective in the treatment of e-waste is to capture the bromine released from the brominated flame retardants (BFRs) added to the polymeric constituents of printed circuits boards (PCBs) and to produce pure bromine-free hydrocarbons. Metal oxides such as calcium hydroxide (Ca­(OH)2) have been shown to exhibit high debromination capacity when added to BFRs in e-waste and capturing the released HBr. Tetrabromobisphenol A (TBBA) is the most commonly utilized model compound as a representative for BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…In another study, GBR was seen to predict the bio-oil yields from hydrothermal liquefaction (HTL) of algae, than RF regression, and this helped optimize the HTL condition for different types of algae from the industry and also implement the ML-based optimization in biofuel production . In fact, in a previous work of our coauthor, they explored the ability of RF, SVR, and linear regression techniques for reproducing the TGA data of tetrabromobisphenol A (TBBPA) combined with Ca­(OH) 2 at 4 different heating rates (opposed to a single heating rate in our present work) under pyrolysis and combustion conditions. Here, we found that the RF model showed the best performance with high prediction accuracies of 0.999, while the SVR also showed good performance with R 2 values of >0.9 for all conditions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In another study, GBR was seen to predict the bio-oil yields from hydrothermal liquefaction (HTL) of algae, than RF regression, and this helped optimize the HTL condition for different types of algae from the industry and also implement the ML-based optimization in biofuel production . In fact, in a previous work of our coauthor, they explored the ability of RF, SVR, and linear regression techniques for reproducing the TGA data of tetrabromobisphenol A (TBBPA) combined with Ca­(OH) 2 at 4 different heating rates (opposed to a single heating rate in our present work) under pyrolysis and combustion conditions. Here, we found that the RF model showed the best performance with high prediction accuracies of 0.999, while the SVR also showed good performance with R 2 values of >0.9 for all conditions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Keeping in mind the discussion in the previous paragraph, we chose to apply an 80:20 split for the calibration/validation data sets with random sampling (data points chosen at random) for our ML models. This was also the industry standard and was chosen due to the large size of our data set . As can be seen in Figure , we applied an 80:20 split for calibrating and validating the models in scenario 1, where the ML models were trained by using the TGA data at each HR for both TBP and TBP + hematite samples.…”
Section: Methods Data Set Splitting Performance Metrics and Workflowmentioning
confidence: 99%
“…Typical model compounds of BFRs include 2,4,6-tribromophenol (TBP) and tetrabromobisphenol-A (TBBA) since they contain a number of brominated phenolic species and aromatics . A plethora of works in literature have focused on the copyrolysis of TBBA with various metal oxides, but very few have focused on TBP. , We would like to highlight a recent work by us, where thermogravimetric analysis (TGA) of TBBA combined with Ca­(OH) 2 was investigated and various machine learning (ML) techniques were applied to reproduce the TGA data . This work was an extension of a previous work also by Ali et al, where TGA data were obtained for samples of both pure TBBA and TBBA combined with Ca­(OH) 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations